2022
DOI: 10.1002/ps.7168
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐ and killed prey‐induced fears bear significant cost to an invasive spider mite: Implications in pest management

Abstract: BACKGROUND The success of biological control using predators is normally assumed to be achieved through direct predation. Yet it is largely unknown how the predator‐ and killed prey‐induced stress to prey may contribute to biological control effectiveness. Here, we investigate variations in life‐history traits and offspring fitness of the spider mite Tetranychus ludeni in response to cues from the predatory mite Phytoseiulus persimilis and killed T. ludeni, providing knowledge for evaluation of the nonconsumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…We further reveal that PTM adults that developed from the fourth‐instar larvae that were exposed to parasitism/predation risk during feeding (Experiment 3) or parasitized by P. zhonghuajia females for a short period of time (i.e., 30 or 60 min in Experiment 4) had significantly lower fecundity and/or shorter adult longevity compared to the controls (Tables 1 and 2), supporting the finding that sublethal stress reduces host survival and reproduction, as reported in many studies 58,75–79 . As reported in other ectophagous idiobiont parasitoids, 47–54 P. zhonghuajia females inject venom to paralyze hosts and suppress their immune responses 29,31 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We further reveal that PTM adults that developed from the fourth‐instar larvae that were exposed to parasitism/predation risk during feeding (Experiment 3) or parasitized by P. zhonghuajia females for a short period of time (i.e., 30 or 60 min in Experiment 4) had significantly lower fecundity and/or shorter adult longevity compared to the controls (Tables 1 and 2), supporting the finding that sublethal stress reduces host survival and reproduction, as reported in many studies 58,75–79 . As reported in other ectophagous idiobiont parasitoids, 47–54 P. zhonghuajia females inject venom to paralyze hosts and suppress their immune responses 29,31 .…”
Section: Discussionsupporting
confidence: 88%
“…Nutrients used for host feeding by parasitoids will not be available for the survival and reproduction of hosts. We further showed that PTM females also had significantly lower reproductive output when their mothers experienced predation risk (Table 2), indicating that nonconsumptive impacts on prey may be transgenerational 78–81 …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In biocontrol, more generally, the ways in which risk-induced trait responses might mitigate or amplify management practices are being increasingly recognised (Culshaw-Maurer et al, 2020), and NCEs have now been observed in many agricultural pest species. For example, effects of risk-induced trait responses on pest demographic rates have been demonstrated in aphids (Bannerman et al, 2011;Fievet et al, 2008;Nelson, 2007), spider mites (Gyuris et al, 2017;Ristyadi et al, 2022), planthoppers (Wen & Ueno, 2021) and lepidopterans (Griffin & Thaler, 2006;Xiong et al, 2015). Risk-induced stress responses, and predator avoidance behaviours in particular, can be leveraged to reduce pest populations by deploying predator cues (e.g., pheromones) rather than predators themselves (Aflitto & Thaler, 2020).…”
Section: Discussionmentioning
confidence: 99%